A Study of the Efficiency of Line Plot Surveys in Forest Enumerations - Chacko, V. J.; Mukerji, H. K.; Mitra, S. N. (Indian Forester, 1965)
The paper gives the results of a study on the precision of the estimate of mean from sub sampling of strips obtained as a stratified random sample of plots within strips as compared to Random line plot and Partially systematic sampling. It has been found from the analysis of a complete enumeration data of Mount Stuart, Madras and a 20 % systematic strip enumeration data of 'sal' from Uttar Pradesh, that stratified random sampling within strips gives more precise results than that of Random line plot sampling for any intensity of samping but less precise than that of Partially systematic sampling when the intensity of sampling within strips is lower than 1 in 6.